2022
DOI: 10.3390/ijms23126571
|View full text |Cite
|
Sign up to set email alerts
|

Brexpiprazole Reduces 5-HT7 Receptor Function on Astroglial Transmission Systems

Abstract: Several atypical antipsychotics exert mood-stabilising effects via the modulation of various monoamine receptors and intracellular signallings. Recent pharmacodynamic studies suggested that tripartite synaptic transmission can contribute to the pathophysiology of schizophrenia and mood disorders, their associated cognitive impairment, and several adverse reactions to atypical antipsychotics. Therefore, to explore the mechanisms underlying the antidepressive mood-stabilising and antipsychotic effects of brexpip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(32 citation statements)
references
References 80 publications
0
32
0
Order By: Relevance
“…An Akt inhibitor, 10-[4-(N,N-diethylamino)butyl]-2-chlorophenoxazine hydrochloride (DEBC: 10 μM), Erk inhibitor, 5-(2-Phenyl-pyrazolo[1,5-a]pyridin-3-yl)-1H-pyrazolo[3,4-c]pyridazin-3-ylamine (FR180204: 20 μM) [ 18 , 31 , 39 , 40 , 52 ] and AMPK inhibitor, dorsomorphin (10 μM) [ 54 ], also did not affect basal astroglial D-serine release ( Figure 1 B), whereas ripple-burst evoked D-serine release was inhibited by 10 μM DEBC and 20 μM FR180204, but was not affected by 10 μM dorsomorphin ( Figure 1 C).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…An Akt inhibitor, 10-[4-(N,N-diethylamino)butyl]-2-chlorophenoxazine hydrochloride (DEBC: 10 μM), Erk inhibitor, 5-(2-Phenyl-pyrazolo[1,5-a]pyridin-3-yl)-1H-pyrazolo[3,4-c]pyridazin-3-ylamine (FR180204: 20 μM) [ 18 , 31 , 39 , 40 , 52 ] and AMPK inhibitor, dorsomorphin (10 μM) [ 54 ], also did not affect basal astroglial D-serine release ( Figure 1 B), whereas ripple-burst evoked D-serine release was inhibited by 10 μM DEBC and 20 μM FR180204, but was not affected by 10 μM dorsomorphin ( Figure 1 C).…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, a 5-HT7R and 5-HT transporter-inhibiting antidepressant, vortioxetine [ 36 , 37 ], suppresses astroglial L-glutamate release via inhibition of connexin43 (Cx43) trafficking to the plasma membrane [ 31 ]. Similar to vortioxetine, mood-stabilising antipsychotics, such as brexpiprazole and lurasidone, which are effective for bipolar depression but not for mania, also suppress astroglial L-glutamate release due to the same mechanism [ 18 , 28 , 38 , 39 , 40 , 41 ]. It has been demonstrated that 5-HT7R inhibition probably plays an important role in the underlying effects of vortioxetine, brexpiprazole and lurasidone on the suppression of Cx43 trafficking [ 31 , 38 , 39 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations